2018
DOI: 10.1161/circresaha.118.311378
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Vascular Aging

Abstract: Aging of the vasculature plays a central role in morbidity and mortality of older people. In order to develop novel treatments for amelioration of unsuccessful vascular aging and prevention of age-related vascular pathologies it is essential to understand the cellular and functional changes that occur in the vasculature during aging. In this review, the pathophysiological roles of fundamental cellular and molecular mechanisms of aging, including oxidative stress, mitochondrial dysfunction, impaired resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
580
3
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 622 publications
(609 citation statements)
references
References 251 publications
(335 reference statements)
12
580
3
14
Order By: Relevance
“…Studies support that mtROS contribute to the inflammation in the cardiovascular system [17]. mtROS activate the redoxsensitive mediator, nuclear factor-κB (NF-κB), which regulates the transcription of various proinflammatory cytokines 2 Oxidative Medicine and Cellular Longevity [11,18]. As the heart ages, prolonged exposure to high levels of oxidants leads to the activation of NF-κB-mediated inflammation.…”
Section: Inflammation In Cardiacmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies support that mtROS contribute to the inflammation in the cardiovascular system [17]. mtROS activate the redoxsensitive mediator, nuclear factor-κB (NF-κB), which regulates the transcription of various proinflammatory cytokines 2 Oxidative Medicine and Cellular Longevity [11,18]. As the heart ages, prolonged exposure to high levels of oxidants leads to the activation of NF-κB-mediated inflammation.…”
Section: Inflammation In Cardiacmentioning
confidence: 99%
“…Enzymes of the electron transport system reside on the inner mitochondrial membrane (IMM), encompassing the mitochondrial matrix containing mtDNA. Excessive mitochondrial reactive oxygen species (mtROS) can damage DNA [11,12]. The mtDNA damage, which reduces the stabilization of adequate ATP supply during cardiac aging, disrupts the balance of cellular apoptosis, mitochondrial bioenergetics, and biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Altered energy metabolism may also be a key contributor to brain endothelial ageing 42 . We found that respiratory electron transport chain / ATP synthesis (e.g.…”
Section: Zonation-dependent Functional Changes Implicated In Aged Bramentioning
confidence: 99%
“…Aging-induced functional and structural changes of vasculatures contribute to the pathogenesis of a wide range of age-related diseases, including ASCVD. Cellular senescence is a fundamental aging process wherein cells, including vascular endothelial and smooth muscle cells (vascular senescence 4) ), permanently withdraw from the cell cycle in response to a range of endogenous and exogenous stressors and undergo distinctive phenotypic alterations, including profound pro-inflammatory secretome changes 5) .…”
Section: Vascular Senescence Sirt1 and Ascvdmentioning
confidence: 99%